Flexible photonic crystal membranes with nanoparticle high refractive index layers - Karrock, Torben; Paulsen, Moritz; Gerken, Martina (Beilstein Journal of Nanotechnology, 2017)
Flexible photonic crystal slabs with an area of 2 cm2 are fabricated by nanoimprint replication of a 400 nm period linear grating nanostructure into a ≈60 µm thick polydimethylsiloxane membrane and subsequent spin coating of a high refractive index titanium dioxide nanoparticle layer. Samples are prepared with different nanoparticle concentrations. Guided-mode resonances with a quality factor of Q ≈ 40 are observed. The highly flexible nature of the membranes allows for stretching of up to 20% elongation. Resonance peak positions for unstretched samples vary from 555 to 630 nm depending on the particle concentration. Stretching results in a resonance shift for these peaks of up to ≈80 nm, i.e., 3.9 nm per % strain. The color impression of the samples observed with crossed-polarization filters changes from the green to the red regime. The high tunability renders these membranes promising for both tunable optical devices as well as visualization devices.
Keywords: fabrication; flexible membrane; nanostructure; photonic crystal; resonance shift